Pengembangan Aplikasi Simulasi Berbasis Web terhadap Kompetensi Kognitif Crimping Kabel UTP Siswa SMK - Wibawa, Ramadhan Cakra; Baihaqi, Ahmad Zulkifli; Herlambang, Yudha Bima; Rahmawati, Cahya Dwi; Pratama, Muhammad Angga (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
In the field of computer networks and telecommunications, one of the basic skills that must be mastered is the installation of UTP (Unshielded Twisted Pair) cables. This skill is the main foundation in building network systems. However, in practice, the learning process often faces obstacles. Limited practice equipment, the risk of student errors that can cause equipment damage, and short learning times make it difficult for students to understand the concept in depth. This condition causes some students to have difficulty understanding the procedures and logic of UTP cable installation. To address these challenges, this study developed and tested a web-based simulation application called